Mangrove Tannis As Corrosion Inhibitors In Acidic Medium - Study Of Flavanoid Monomers. - A., Abdul Rahim; E., Rocca; J., Steinmetz; R., Adnan; M.J., Kassim (2004)
Study of organic corrosion inhibitors is an interesting field of research due to its usefulness in various industries. Most of the well known efficient inhibitors in acidic media are organic compounds that contain nitrogen, sulfur, oxygen and multiple bonds in the molecules which are adsorbed on the metal surface and are used as temporary protectors or in cooling water systems.